2016
DOI: 10.1007/s11214-016-0288-6
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Ray Bursts and the Early Star-Formation History

Abstract: We review the uncertainties in high-z star-formation rate (SFR) measures and the constraints that one obtains from high-z gamma-ray burst (GRB) rates on them. We show that at the present time, the GRB rates per unit star-formation at z > 3 are higher than at lower redshift. There could be a multitude of reasons for this: a stellar metallicity bias for GRB production, a top-heavy initial mass function (IMF) and/or missing a significant fraction of star-formation in field galaxy surveys due to incompleteness, su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 73 publications
0
10
1
Order By: Relevance
“…Behroozi & Silk (2015) used the updated SFH normalisation from Behroozi et al (2013) to scale down the GRB-inferred SFH of Kistler et al (2013) at z > 4, making them more consistent with their inferred SFH fit. In a recent review, though, Chary et al (2016) show that metallicity constraints at z > 2 from damped Lyα systems are consistent with the rather more elevated SFH inferred by Kistler et al (2013), and consistent with that of Gruppioni et al (2013) and Rowan-Robinson et al (2016) than the lower SFH of Behroozi & Silk (2015). It is noteworthy in this discussion that the radio luminosity function results of Novak et al (2017) are also consistent with the GRB-inferred SFR densities (Chary, Berger, & Cowie 2007;Yüksel et al 2008;Kistler et al 2009Kistler et al , 2013 at these high redshifts, reinforcing the expectation of a steepening low luminosity tail to the high redshift galaxy luminosity function (Kistler et al 2013;Bouwens et al 2015a).…”
Section: Imf Measurement Approaches: Cosmic Census Techniquesmentioning
confidence: 99%
“…Behroozi & Silk (2015) used the updated SFH normalisation from Behroozi et al (2013) to scale down the GRB-inferred SFH of Kistler et al (2013) at z > 4, making them more consistent with their inferred SFH fit. In a recent review, though, Chary et al (2016) show that metallicity constraints at z > 2 from damped Lyα systems are consistent with the rather more elevated SFH inferred by Kistler et al (2013), and consistent with that of Gruppioni et al (2013) and Rowan-Robinson et al (2016) than the lower SFH of Behroozi & Silk (2015). It is noteworthy in this discussion that the radio luminosity function results of Novak et al (2017) are also consistent with the GRB-inferred SFR densities (Chary, Berger, & Cowie 2007;Yüksel et al 2008;Kistler et al 2009Kistler et al , 2013 at these high redshifts, reinforcing the expectation of a steepening low luminosity tail to the high redshift galaxy luminosity function (Kistler et al 2013;Bouwens et al 2015a).…”
Section: Imf Measurement Approaches: Cosmic Census Techniquesmentioning
confidence: 99%
“…In this section, I provide an overview of our current understanding of the environments traced by GRBs, and of the selection effects to be aware of in a GRB-selected galaxy sample. For a more detailed and very comprehensive review on the use of GRBs to study the cosmic SFR density, I redirect the reader to [187].…”
Section: The Environments Traced By Long-duration Gamma-ray Burstsmentioning
confidence: 99%
“…Because long gamma-ray bursts (lGRBs) are the most luminous explosions in the universe and because of definitive E-mail: lloyd-ronning@lanl.gov evidence of their association with massive star progenitors (Galama et al 1998;Hjorth et al 2003;Woosley & Bloom 2006;Hjorth & Bloom 2012), they have long been suggested as tools with which to estimate the high redshift star formation rate (Lloyd-Ronning et al 2002;Jakobsson et al 2005;Kistler et al 2008;Yüksel et al 2008;Kistler et al 2009;Wanderman & Piran 2010;Robertson & Ellis 2012;Trenti et al 2013;Lien et al 2014;Petrosian et al 2015;Chary et al 2016;Kinugawa et al 2019). However, there are a number of issues that make doing so difficult, essentially related to understanding exactly what types of stars and/or fractions of the global stellar population produce GRBs (including accounting for multiple GRB progenitors), and understanding how this relationship may change over cosmic time.…”
Section: Introductionmentioning
confidence: 99%